Biomechanical evaluation and surface characterization of a nano-modified surface on PEEK implants: a study in the rabbit tibia - Johansson P (Dove Medical Press, 2014)
Pär Johansson,1 Ryo Jimbo,1 Per Kjellin,2 Fredrik Currie,2 Bruno Ramos Chrcanovic,1 Ann Wennerberg1 1Department of Prosthodontics, Faculty of Odontology, Malmö University, Malmö, Sweden; 2Promimic AB, Göteborg, Sweden Abstract: Polyether ether ketone (PEEK) is today frequently used as a biomaterial in different medical operations due to its excellent mechanical and chemical properties. However, the untreated surface of PEEK is bioinert and hydrophobic, and it does not osseointegrate in its pure form. The aim of this study was to evaluate a unique nano-modified surface of PEEK with respect to osseointegration. Forty-eight threaded, non-cutting PEEK implants were inserted bilaterally in the tibia of 24 rabbits. Half of the implants (n=24) were coated with nanocrystalline hydroxyapatite (test) and the remaining implants (n=24) were left uncoated (control). Half of the animals (n=12) were euthanized after 3 weeks of healing and the remaining (n=12) after 12 weeks. The implant retention was measured with a removal torque apparatus. Surface analysis was performed with interferometry, scanning electron microscopy, and X-ray photon spectroscopy to relate the removal torque to the applied surface. The test implants revealed a significantly higher retention after 3 weeks (P=0.05) and 12 weeks (P=0.028) compared to controls. The result of the present study proves that the addition of nanocrystalline hydroxyapatite coating to PEEK surfaces significantly increases its removal torque and biocompatibility. Keywords: polyether ether ketone, hydroxyapatite, removal torque, nanotopography